Edukasi Menstruasi Melalui Media Poster dan Powerpoint (PPT) Meningkatkan Pengetahuan dan Kesiapan Siswa Menghadapi Menarche - Silpia Utami, Sang Ayu Putu; Astuti, Ika Widi; Juniartha, I Gusti Ngurah; Sanjiwani, Ida Arimurti (Jurnal Gema Keperawatan, 2023)
Menarche is the first menstruation that occurs in the age range of 10-16 years. Early adolescents will experience significant physical, mental and social changes during puberty. Lack of information about menstruation can make it difficult for children to accept menarche. Health education is a process of raising public awareness by providing knowledge to change behavior for the better. The purpose of this study was to analyze the effect of education about menstruation using posters and power point media on knowledge and readiness to face menarche. The research design was a pre-experiment with a one-group pretest-posttest approach. Respondents were students in grades IV, V, VI at SD Negeri 2 Tusan who had not experienced menarche, totaling 26 people and were selected using total sampling. The results of the Wilxocon test on the knowledge variable showed that there was a significant difference between before and after being given education about menstruation (p = 0.000). Then the results of the Paired Sample T-Test on the readiness variable showed that there was a significant difference between before and after being given education (p = 0.000). Therefore, it can be concluded that the provision of interventions in the form of education about menstruation using posters and power point media has an effect on increasing knowledge and readiness to face menarche in female students entering puberty. Health promotion using posters and power point media can be used as a medium for adolescents to understand the importance of readiness from various aspects in facing menarche. This research can enrich knowledge in the field of maternity nursing related to reproductive health.